In Silico Study of Bioactive Compounds from Syzygium malaccense Targeting HER2 and Progesterone Receptors in Breast Cancer - Nawadhir Fauzan; Riska Prasetiawati; Meilia Suherman; Dhania Novitasari; Muchtaridi Muchtaridi (Indonesian Society for Cancer Chemoprevention, 2025)
Breast cancer remains one of the most common causes of cancer-related deaths among women, with progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) being key molecular targets in its progression. This study aimed to explore the potential of bioactive compounds from Syzygium malaccense that have exhibited anticancer activities, as targeted inhibitors for PR and HER2, using computational approaches. A total of 155 compounds were initially screened for anticancer potential using the Prediction of Activity Spectra for Substances (PASS), identifying 80 compounds for further analysis. Drug-likeness and pharmacokinetic predictions indicated that several compounds complied with the Rule of Five (RO5) and had favorable absorption and distribution profiles, suggesting their suitability as oral drug candidates. Molecular docking revealed that quercetin exhibited favorable interactions with PR, particularly involving the ARG 766 residue, while myricetin demonstrated strong binding affinity to HER2, surpassing trastuzumab, and interacting with key residues Asp 863, Lys 753, Ala 751, and Leu 796. Molecular dynamics simulations confirmed the stability of the Myricetin-HER2 complex under physiological conditions over 15 ns, supporting its potential as a HER2 inhibitor. These findings highlight myricetin and quercetin as promising natural compounds for breast cancer therapy targeting HER2 and PR, respectively. However, further experimental validation, including in vitro and in vivo studies, is necessary to confirm their therapeutic efficacy and safety. Overall, this study supports Syzygium malaccense as a valuable source of natural bioactive compounds for breast cancer drug discovery.Keywords: in silico screening, Syzygium malaccense, breast cancer, progesterone receptor, HER2.